Programa de coleta seletiva solidária da Universidade Federal da Paraíba - UFPB: avanços e desafios da gestão ambiental - Costa, Tarcísio Valério da (2019)
The sustainable development of a country necessarily includes the involvement of universities, through their regimental functions of teaching, research and extension. For its operation, the university demands natural resources such as water, energy, food circulation, in addition, to manipulation laboratory products, urban solid waste production and connection with fauna and flora. Where they are likely to generate environmental impacts if they do not have an environmentally destination or treatment. In this context, this study has as aim to analyze the Program of Solidary Selective Collection of recyclable solid wastes of the Federal University of Paraíba - FUPB, Campus I. According to the current legislation and its social and environmental impacts, and also proposes suggestions for the improvement of the Program. The methodology combined qualitative and quantitative approaches. The procedures were documentary research of secondary data, systematic observation and field research, with a non-probabilistic sampling from university actors involved through questionnaires and a semi-structured interview. The study was performed at the Federal University of Paraíba, Campus I. The results were obtained in 2016 until 2018, with a total of 66.64 tons of recycled material. Where the both years were transferred to ASCARE-JP, a collector's Association that is marketed, generating income to them. In the environmental aspect, selective collection also contributed to the reduction of greenhouse gas emissions, in terms of tons of carbon dioxide equivalent (tCO2e). However, the field research conducted with the teachers, students and technical administrators, regarding the perception about the FUPB campus I selective collection program, showed that the system needs some adjustments, considering 67.16% of respondents no one knows of its existence. 87.5% are unaware of any environmental education programs developed; 73.7% do not know the program institutionally and therefore 83.96% do not know of the current legislation (Decree No. 5.940 / 2006). However, 93.00% consider the participation of waste pickers important in the process of selective collection. Thus, challenging paths were found for the consolidation of solidary selective collection at UFPB, campus I, embracing the scope of environmental management, where we suggest at the conclusion of this work to better address environmental, economic and social sustainabilit